Leaders and Managers Styles towards Employee Centricity: A Study of Hospitality Industry in United Arab Emirates - Matira, Kristelle Marjori; Awolusi, Olawumi Dele (Information Management and Business Review, 2020)
Different styles of leadership have emerged within different studies and have been proven in different ways throughout the years. Aim of this study was to identify the effect of leadership styles towards employee centricity within the Hospitality Industry in UAE. Study’s conceptualization was derived from Burns (1978) theory on circulating the influences, inspirations, motivations, encouragements and consideration where behaviors such empathy, optimism, enthusiasm and openness are nurtured. Multiple regression analysis was applied to understand the influence of the analytical variables and target variable (employee centricity). Total 172 responses from different hotels were collected using survey questionnaires. Mixed method then was used to validate attributes from different parties to provide deeper insights of the given problem. Findings, based on the research data and as validated by the regression results, therefore revealed that employees, centricity greatly influenced the level of the employee satisfaction and motivation within the industry of study. Lack of trust, respect, engagement and motivation soars the big picture. Due to different aspect of responsibilities leaders and managers are entitled with, not every employee is given the proper attention and leniency over their issues. Research concluded that managers and leaders are great influence to employees which builds employee centricity as a whole. Consequently, employee centricity has to consider a bigger factor reclined from different characteristics of a manager’s responsibilities, relationship and provisions. This is found out to incorporate factors, like purpose and autonomy, rewards, recognition, development and growth that may encourage employees to work effectively and efficiently.